A major contribution to Song of Songs scholarship - Sasson, Jack M. (JAOS, 1987)
This article welcomes M. Fox's, The Song of Songs and the Ancient Egyptian Love Songs; but it also critically reviews his initial assumptions regarding the relationship between Hebrew and Egyptian love poetry. It then proceeds to suggest alternate ways of understanding a number of cruxes in canticles.